THE ROLE OF REAP (READ, ENCODE, ANNOTE, AND PONDER) TECHNIQUE IN TEACHING READING COMPREHENSION AT ONE STATE SENIOUR HIGH SCHOOL OF SINTANG - Tuti Tuti; Sijono Sijono; Henry Elisa; Selvina Semu Meko (Journal of English Educational Study (JEES), 2023)
Abstract: This research focused on solving the students’ difficulties in understanding the meaning and finding information from a text. The objective of this research was to recognize the improvement of the student’s participation and the student reading performance in teaching reading comprehension through REAP technique. The research design used was Classroom Action Research (CAR). The data was collected using; observation, interviews, tests, and documentation. The findings showed there was an improvement in student’s ability to comprehend a reading text. The student’s involvement in teaching and learning activities improved as well. Most of the students gave a positive response to the teaching-learning process. It could be concluded that the REAP technique was useful to be used in teaching and learning reading comprehension at one state senior high school. The students became active and began to think critically. REAP technique can be an alternative as a teaching medium specifically for reading comprehension. Keywords: Reap Technique, Reading comprehension, Classroom Action Research